2020
DOI: 10.1111/joes.12395
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparities in International Research Collaboration: A Study of 25,000 University Professors

Abstract: In this large-scale research based on bibliometric, biographical and administrative data, we examine how gender disparities in international research collaboration differ by collaboration intensity, academic position, age, and academic discipline. The following are the major findings: (1) While female scientists exhibit a higher rate of general, national, and institutional collaboration, male scientists exhibit a higher rate of international collaboration. (2) An aggregated picture of gender disparities hides … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 84 publications
2
49
0
6
Order By: Relevance
“…Engineers who were men continued to be paid more than women engineers (Wahrenburg & Weldi, 2007). Moreover, women are promoted less frequently, win fewer research grants when they stay in academia (Nimmesgern, 2016), establish fewer international collaborations (Zippel, 2017), and show less international collaboration patterns than men (Kwiek & Roszka, 2020;Larivière et al, 2013), which is a crucial driver for academic career development and scientific productivity (Wagner, 2018).…”
Section: Why Study Stem? (Under)employment Opportunities In Germanymentioning
confidence: 99%
“…Engineers who were men continued to be paid more than women engineers (Wahrenburg & Weldi, 2007). Moreover, women are promoted less frequently, win fewer research grants when they stay in academia (Nimmesgern, 2016), establish fewer international collaborations (Zippel, 2017), and show less international collaboration patterns than men (Kwiek & Roszka, 2020;Larivière et al, 2013), which is a crucial driver for academic career development and scientific productivity (Wagner, 2018).…”
Section: Why Study Stem? (Under)employment Opportunities In Germanymentioning
confidence: 99%
“…In particular, most of the previous studies were conducted with a focus on academic career stories of women, women, and leadership, the relationship between career and balance for women (Betz & Fitzgerald, 1987;Eagly & Carli, 2007;Hacıfazlıoglu, 2010;Hoskins, 2015;Madsen, 2008;Ozkanlı & White, 2009;Tucker & Bryan, 1991). Some research has emphasized the subjects of gender and scientific careers (Fox, 2020;Huang et al, 2020), gender disparities in international research collaboration (Kwiek & Roszka, 2020), women academics and research productivity (Aiston & Jung, 2015) while others has focused on a Bordieuan lens and women (Acker, 2010;Blackmore & Sachs, 2007;Bourdieu & Wacquant, 1992;Tasci-Kaya, 2016). Considering this background in literature, some feminist scholars (Armstrong, 2020;Arnot & Weiner, 1987;Barrett, 1988;Breeze & Taylor, 2020;Erny, 2014;Holvino, 2010;Lorber, 2010;Nehere, 2016;Stevi, 1998;Van Zoonen, 2002;Young, 1986) have considered that women are under-represented in academia.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific studies on gender productivity, collaborations, and recent assessments of gender inequalities show that these concepts have changed over time, albeit slowly (Huang et al, 2020;Kwiek & Roszka, 2020). In particular, a study found that Polish women academics constitute a productive and internationalized part of Polish academicians (43.6%), and Poland has a relatively high proportion of professors compared to most Western European countries (Kwak & Roszka, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations